Very Late Relapse in Pediatric Acute Myeloid Leukemia: A Case Report and Brief Literature Review. Issue 6 (August 2021) - Unis, Graham D.; VanderVeen, Nathan; Fletcher, Matthew; Vasquez, Robert J.
Abstract : Acute myeloid leukemia (AML) is a heterogenous group of diseases affecting ~500 children in the United States annually. With current therapy, 90% of these children will obtain complete remission. However, 30% to 40% of these patients will relapse, most commonly within the first 3 years. Very late relapses, defined as relapse occurring >5 years after complete remission, are rare, accounting for 1% to 3% of relapses. We describe a patient with AML harboring an AFDN/KMT2A translocation who relapsed 12 years after matched sibling stem cell transplant, provide a brief review of the relevant literature, and describe proposed mechanisms to explain very late relapse AML.